Practicing Stalinism : Bolsheviks, boyars, and the persistence of tradition - Getty, J. Arch (John Arch), 1950- (Yale University Press, 2013)
In old Russia, patron/client relations, 'clan' politics, and a variety of other informal practices spanned the centuries. Government was understood to be patrimonial and personal rather than legal, and office-holding was far less important than proximity to patrons. Working from heretofore unused documents from the communist archives, J. Arch Getty shows how these political practices and traditions from old Russia have persisted throughout the 20th-century Soviet Union and down to the present day.